Eligibility for subcutaneous implantable cardioverter‐defibrillator in adults with congenital heart disease. (3rd February 2021) - Zormpas, Christos; Silber‐Peest, Ann Sophie; Eiringhaus, Jörg; Hillmann, Henrike A.K.; Hohmann, Stephan; Müller‐Leisse, Johanna; Westhoff‐Bleck, Mechthild; Veltmann, Christian; Duncker, David
Abstract: Aims: Patients with adult congenital heart disease (ACHD) carry an increased risk for sudden cardiac death. Implantable cardioverter‐defibrillator (ICD) therapy may be challenging in these patients due to anatomical barriers, repeated cardiac surgery, or complicated transvenous access. Thus, the subcutaneous ICD (S‐ICD) can be a promising alternative in this patient population. Patients with ACHD show significant electrocardiogram (ECG) abnormalities, which could affect S‐ICD sensing because it depends on surface ECG. Methods and results: One hundred patients with ACHD were screened for S‐ICD eligibility. Standard ECG‐based screening test and automated S‐ICD screening test were performed in all patients. Sixty‐six patients (66%) were male. Underlying congenital heart disease (CHD) was mainly CHD of great complexity (71%) and moderate complexity (29%), including repaired tetralogy of Fallot (20%), which was the most common entity. Thirty‐seven patients (37%) already had a pacemaker (23%) or ICD (14%) implanted. Automated screening test identified 83 patients (83%) eligible for S‐ICD implantation in either left parasternal position (78%) or right parasternal position (75%). Absence of sinus rhythm, QRS duration, and a paced QRS complex were associated with S‐ICD screening failure in univariate analysis. Receiver operating characteristic curve and multivariate analysis revealed a QRS duration ≥148 ms as the only independent predictor for S‐ICD screening failure. Conclusions: Patients with ACHD show satisfactory eligibility rates (83%) for S‐ICD implantation utilizing the automated screening test, including patients with CHD of high complexity. S‐ICD therapy should be considered with caution in ACHD patients with a QRS duration ≥148 ms and/or need for ventricular pacing.